Aerated biofilters with multiple-level air injection configurations to enhance biological treatment of methane emissions. (September 2017) - Farrokhzadeh, Hasti; Hettiaratchi, J. Patrick A.; Jayasinghe, Poornima; Kumar, Sunil
Highlights: Methane biofilter performance was improved through multiple-level aeration design. A comprehensive set of statistically-designed lab experiments were conducted. 2-Level aerated biofilter showed a higher oxidation than the other studied biofilters. Abstract: Aiming to improve conventional methane biofilter performance, a multiple-level aeration biofilter design is proposed. Laboratory flow-through column experiments were conducted to evaluate three actively-aerated methane biofilter configurations. Columns were aerated at one, two, and three levels of the bed depth, with air introduced at flow rates calculated from methane oxidation reaction stoichiometry. Inlet methane loading rates were increased in five stages between 6 and 18 mL/min. The effects of methane feeding rate, levels of aeration, and residence time on methane oxidation rates were determined. Samples collected after completion of flow-through experiments were used to determine methane oxidation kinetic parameters, Vmax, Km, and methanotrophic community distribution across biofilter columns. Results obtained from mixed variances analysis and response surfaces, as well as methanotrophic activity data, suggested that, biofilter column with two aeration levels has the most even performance over time, maintaining 85.1% average oxidation efficiency over 95 days of experiments.